The Analysis of E-Government Policy in Supporting of Public Information Transparency of the Wajo Regency Government - Alam, Andi Samsu; As, Hasri; Rusli, A.M. (International Journal of Psychosocial Rehabilitation, 2020)
The analysis of E-government policy in supporting public information transparency of the Wajo regency government. This study aims to study and analyze the application of E-Government policies in Wajo Regency in terms of institutional, policy, planning, application and infrastructure aspects. The type of research used in this study is qualitative, which will provide a factual description of the E-Government policy in Wajo District. The results of this study indicate that: In the implementation of Wajo District Head Regulation No.13 of 2018 Concerning General Policies on the Implementation of E-Government in Local Government Environments within the scope of government Not yet effective in its implementation. based on the aspects used in this study shows the implementation of E-Government in the institutional, policy, planning, application and infrastructure aspects still Wajo District Government presents PINDU as a forum for the public to easily reach out and obtain the information needed, and participate to encourage quality improvement public services by implementing systems based on on-line and supported by modern technology devices. The interests of Wajo community members will be provided and served well in a simple, easy and effective way